Recommended minimum data to be collected in research studies on Alzheimer's disease. The MRC (UK) Alzheimer's Disease Workshop Steering Committee. - Wilcock, G K (1989)
In order to be able to compare the results of research work carried out in different centres on Alzheimer's disease and dementia, it is necessary for there to be standardised assessment methods. The Medical Research Council organised a workshop in order to see whether workers in Britain in the field of dementia research could agree on such standardised assessment methods. The workshop agreed guidelines for the minimum data which should be collected, in clinical and pathological studies, on patients with presumed Alzheimer's disease and dementia. These recommendations are compared with other approaches based on research diagnostic criteria.